Synthesis A Flexible Conductive Film of Poly 3,4-Ethylenedioxythiophene Polystyrene Sulfonate (PEDOT: PSS) Using Spray Pyrolysis Method - Tarmidzi, Fadhil Muhammad; Sasongko, Setia Budi (Center of Biomass & Renewable Energy, Diponegoro University, 2018)
Popularity of conducting polymers are become widely known and researches for practical application also has been done. In order to developed a continuous process for industrial scale,Â we have proposed a spray pyrolysis method to synthesis a flexible conductive film of Poly(3,4-ethylenedioxythiophene) poly(styrene sulfonate) (PEDOT:PSS) on poly(ethylene terephthalate) (PET) and annealed at different temperatures and spray distances. The optimum condition that resulting a best morphology was anneal at 90oC and 20 cm distance with electrical conductivity 4.5 S/cm. It was found that annealing at temperature higher than 90oC will resulting a stress to a film and formed crack due to a different thermal expansion, while at the distance higher than 20 cm resulting a loss of PEDOT:PSS droplets. IR spectra shows that there is no any sign of PEDOT:PSS degradation even at 110oC. SEM analysis also show that the thickness is well distributed and there is no any sign of crack formedArticle History: Received February 24th 2017; Received in revised form May 16th 2018; Accepted May 20th 2018; Available onlineHow to Cite This Article: Tarmidzi, F.M. and Sasongko, S.B. (2018) Synthesis A Flexible Conductive Film of Poly 3,4-Ethylenedioxythiophene Polystyrene Sulfonate (PEDOT:PSS) Using Spray Pyrolysis Method. Int. Journal of Renewable Energy Development, 7(2), 159-162.https://doi.org/10.14710/ijred.7.2.159-162